A Study on Intelligent GIS Installation System Based on Six-DOF Parallel Multi-axis Motion Control - Liu, Ti; Mao, Hongwei; Lei, Dong; Li, Boming; Fu, Dahong (Journal of physics. Conference series, 2021)
Aiming at the connection of pipelines during the GIS installation process of power transmission and transformation projects, this subject designs and produces an intelligent GIS installation system based on 6-DOF parallel multi-axis motion control, which is applied to practical applications. The intelligent installation system can realize six independent motions and their combined motions in three-dimensional space. Relying on the multi-dimensional visual positioning system, through the six-degree-of-freedom parallel multi-axis motion control system, the precise docking during the installation of the precision GIS cavity can be realized.